The Effect of Worship on Improving the Marital Relationship in Islamic Law : A Legitimate Objectives Study - Shwan Gluk Rafeeq; Hemin Aziz Braem (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Praise be to God, Lord of the Worlds, and prayers and peace be upon the Seal of the Prophets and Messengers, and upon his family, companions, and those who followed them in goodness until the Day of Judgment. Then: Worship has a high status in Islam, which makes it extremely important to talk about it, and no time, place or person is excluded. Praise and worship are the purpose of human creation, as Allah says (Jinn and humans were not created except for worship)(Al-Zari'at: 56), and life has no meaning if worship does not cover all aspects of life. Because it is not limited to worship rituals such as prayer, zakat, Hajj, etc., but its scope is so wide that it covers and organizes every human movement and all aspects of life on them by protecting their religion, mind, money, honor and offspring. This study aims to determine the importance of the family in the Qur'an and Sunnah, and to identify effective tools in improving marriage relationships, and then to identify the psychological and intellectual effects of worship in improving marriage relationships.